Laplace transform-based theoretical foundations and experimental validation-low frequency supercapacitor circulation for efficiency improvements in linear regulators - Kankanamge, K; Kularatna, N; Steyn-Ross, DA (The Institution of Engineering and Technology, 2012)
Supercapacitor circulation techniques can be used to improve the end-to-end efficiency of linear regulators based on commercial low drop-out regulators (LDO). In this approach, one or more supercapacitors are used in series and parallel to the input of an LDO IC, and circulated at a very low frequency to increase the end-to-end efficiency by a multiplication factor compared with the efficiency of a linear regulator circuit with the same input–output voltages. This study presents the essential theory of supercapacitor circulation, together with analytical results and comparisons with experimental measurements from a practical 12–5 V implementation. The new technique achieved overall end-to-end efficiencies in the range of 70 to 80%, compared with the maximum theoretical efficiency of 42% for a 12–5 V linear regulator.
Keywords: Other energy storage; Integral transforms; Capacitors; Power electronics, supply and supervisory circuits